Gold nanoparticles as a promising treatment for diabetes and its complications: Current and future potentials (Brazilian Journal of Pharmaceutical Sciences, 2022)
Diabetes and its complications represent a major cause of morbidity and mortality in diabetes patients. This review is aimed to find the potential of gold nanoparticles (AuNPs) to act as therapeutic agents for diabetes and its complications. Here, we outline the literature related to the self-therapeutic effects of AuNPs. The first goal of this review is to highlight and summarize some of the existing studies (10 years ago) in terms of several parameters such as the size of AuNPs, dose, administration route, experimental model, experimental analysis, and findings. The second goal is to describe the self-therapeutic effects of AuNPs against the pathogenesis determinants of diabetic complications. AuNPs have been found to have inhibitory effects on transforming growth factor-β, antiglycation, antiangiogenic, anti-hyperglycemic, anti-inflammatory, and antioxidant effects. AuNPs treatment effectively disrupts multiple pathogenesis determinants in an animal model of diabetes and diabetic complications. The present review provides insight into the potential applications of AuNPs, which may help reduce the incidence of diabetes and its complications.